2016
DOI: 10.1111/omi.12151
|View full text |Cite
|
Sign up to set email alerts
|

The Porphyromonas gingivalis hemagglutinins HagB and HagC are major mediators of adhesion and biofilm formation

Abstract: Porphyromonas gingivalis is a bacterium associated with chronic periodontitis that possesses a family of genes encoding hemagglutinins required for heme acquisition. In this study we generated ΔhagB and ΔhagC mutants in strain W83 and demonstrate that both hagB and hagC are required for adherence to oral epithelial cells. Unexpectedly, a double ΔhagB/ΔhagC mutant had less severe adherence defects than either of the single mutants, but was found to exhibit increased expression of the gingipain-encoding genes rg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…like gingipains, and potential adhesion molecules such as hemagglutinins, all of which are known as virulence factors (Connolly et al, 2017). The most important virulence factor that P. gingivalis produces is the hemagglutinins (Han, Whitlock, & Progulske-Fox, 1996;Lee, Hillman, & Progulske-Fox, 1996;Shi et al, 1999).…”
mentioning
confidence: 99%
“…like gingipains, and potential adhesion molecules such as hemagglutinins, all of which are known as virulence factors (Connolly et al, 2017). The most important virulence factor that P. gingivalis produces is the hemagglutinins (Han, Whitlock, & Progulske-Fox, 1996;Lee, Hillman, & Progulske-Fox, 1996;Shi et al, 1999).…”
mentioning
confidence: 99%
“…This result is consistent with a previous study by Connolly et al, which showed that P. gingivalis W83 exhibited typical black colonies, whereas ΔhagBΔ-hagC mutant produced white colonies. 3 In addition, our results showed that the parent strain increased the level of ppGpp in response to hemin starvation (Fig. 1b).…”
Section: Discussionmentioning
confidence: 55%
“…1a, while no phenotype was observed in the single mutants, the double mutant (ΔrelΔrshB) exhibited less heme-binding capacity (black pigmentation), especially in broth culture. Since heme plays an essential role in the growth, protection against oxidative stress, and virulence of P. gingivalis, 3,36 we hypothesized that hemin deprivation could be a key stressor that triggers accumulation of (p)ppGpp in P. gingivalis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] In another experiment conducted by Conolly et al [24] Porphyromonas ginggivalis has hemagglutinin protein pili which acts in adhesion on the epitel cell of mouth, colonization, and biofilm formation.…”
Section: Discussionmentioning
confidence: 99%